Removal of Acid Orange 7 dye in a packed bed bioreactor: Process optimization using response surface methodology and kinetic study - Swain G.; Singh S.; Sonwani R.K.; Singh R.S.; Jaiswal R.P.; Rai B.N. (My University, 2025)
The removal of Acid Orange 7 dye was studied in a packed bed bioreactor (PBBR) using bacterial consortium immobilized polyurethane foam (PUF) as packing material. The process variables such as pH, hydraulic retention time, and dye concentration were optimized using response surface methodology (RSM), and optimum conditions were obtained as 7.5, 21.0 h, and 300 mg/L, respectively. The maximum dye removal of 87.31% and chemical oxygen demand (COD) removal of 73.6% were obtained at optimum conditions. The substrate utilization rate was evaluated using the First-order, Second-order, and modified Stover-Kincannon models. The modified Stover-Kincannon and Second-order models showed higher correlation coefficients of 0.993 and 0.983, respectively, for dye removal. The corresponding kinetic parameters were obtained to be: Umax: 0.641 g/L d, KB: 0.602 g/L d for modified Stover-Kincannon model, and Ks: 0.25 L2/gVSS. gCOD. h, n: 0.873, E: 5.890 for Second-order model, respectively. © 2020 Elsevier Ltd